Spatial Spillover Impact of Sectoral Government Expenditure on Poverty Alleviation in South Kalimantan Province - Mega Novitasari; Doddy Aditya Iskandar (The Journal of Indonesia Sustainable Development Planning, 2022)
Poverty is still one of the forefront issues in developing countries. It could hamper the achievement ofsustainable development goals, thereby triggering a recurring call on the government's role in mitigatingpoverty. This paper contributed to the debate on the role of sectoral government spending under thefiscal decentralization policy to combat poverty. Using a case study in South Kalimantan Province, weemployed a spatial panel data analysis covering 13 districts from 2010-2020. This study investigated thepresence of spatial dependency on poverty and the spatial spillover impact of government expenditure—education, health, housing, public facilities, and social protection—on poverty. The research found theexistence of spatial autocorrelation on poverty and the significant high-cluster poverty in the agriculture-based region. The direct estimation from the Spatial Durbin Model uncovered that governmentexpenditure on education, health, and social protection significantly alleviated poverty, while housing andpublic facilities expenditure remained insignificant in reducing the poverty rate. Besides, educationspending also has a significant indirect effect on poverty, indicating the spatial spillover impact ofeducation spending by the neighbors on poverty in a region.